CA-PROM: Validation of a general patient-reported outcomes measure for Chinese patients with cancer. (August 2020) - Hu, Xiaojuan; Zhao, Zhiqiang; Zhang, Shao-Kai; Luo, Yanhong; Yu, Hongmei; Zhang, Yanbo
Highlights: The developed scale was used as an effective evaluation tool for QoL of cancer patients. Two methods, including classical test theory and item response theory (IRT) was used to select items. The method of calculating validity for ordinal categorical PRO data of small sample size: OBID. Explore potential subgroups and determine Risk thresholds of PRO. Abstract: Background: Based the important role of patient-reported outcome in measuring patients' QoL, a general PRO instrument was designed for Chinese patients with cancer. Methods: The instrument was administered in eight hospitals. Based on PRO guidelines, a conceptual framework and item pool were generated after literature review and patients' interviews. Via two-item selection process, the original version of a cancer PRO measure (CA-PROM) was generated. Patients' responsiveness was evaluated in four disease systems by item response theory. The reliability, validity, and feasibility of CA-PROM were assessed. The minimum clinically important differences (MCIDs) and risk thresholds of PRO were calculated. Results: A total of 2213 valid questionnaires were collected. After expert opinions and cognitive tests, 11 items were deleted. In the pre-survey and formal survey, 19 items were deleted based on six methods of classical test theory. In the respiratory, digestive, hematological, and endocrine systems, four items with poor responsiveness were deleted by item response theory. The final CA-PROM included four domains, 13 subdomains, and 49 items. Reliability coefficients of 13 subdomain was > 0.7. The framework of CA-PROM met required criteria by CFA and OBID. The average response time was 14.2 min, indicating feasibility of CA-PROM. The MCIDs were 5.63, 3.42, 4.16 in the physiological, psychological, social domain, respectively. The risk thresholds of PRO for six subdomains were 71.74, 71.28, 66.29, 65.16, 59.56, 66.60, in that order. Conclusion: The developed CA-PROM exhibited good reliability, validity, and feasibility, and can be used as an effective evaluation tool in cancer patients.